PEMBINAAN PASCA IBADAH HAJI MENUJU MABRUR SEPANJANG HAYAT - Zaenal Abidin; Mahrus Ali (Research and Development Center for Guidance for Religious Societies and Religious Services, the Research and Development and Education and Training Agency of the Ministry of Religious Affairs of the Republic of Indonesia (MORA), 2020)
This research is about the challenges of post-hajj fostering to the pilgrims (hujjaj) in Indonesia which are quite large in number. All the pilgrims hope ‘ridha’ of Allah SWT to obtain mabrur pilgrimage. That hope is manifested in the efforts of manasik education and training to ensure the hajj ritual in worship is based on the syariah. The Ministry of Religion on behalf of government currently only provides manasik education and training before the departure of the pilgrimage that organized by the Office of the Ministry of Religion in Regencies / Cities and the Office of Religious Affairs (KUA) in the Districts, and does not conduct post-hajj fostering. Whereas post-hajj fostering is needed by the pilgrims to maintain the sustainability of the mabrur. To this day, the only organization actively carries out post-hajj fostering is the Indonesian Hajj Fraternity Association (IPHI) that is spread throughout the territory of Indonesia (the central board, province board and in almost all regencies / cities and Sub-districts). This post-hajj fostering research is conducted qualitatively by observation, interview and document research. Based on this research it is known that the efforts to develop post-hajj fostering in order to achieve mabrur throughout life is a formidable challenge that needs the support of society and government.